Establishment and development of approaches to technical monitoring of building assets through conceptual-categorial analysis and factors of actualization - Yakymchuk, I.; Kroshka, Y.; Polischuk, O.; Ostapenko, I.; Legkov, V. (Ways to Improve Construction Efficiency, 2024)
The establishment and development of approaches to technical monitoring of building assets is a key factor in ensuring safety, operational efficiency, and long-term sustainability of construction resources. In the context of accelerated urbanization, intensive use of engineering structures, and increased requirements for the safe and energy-efficient utilization of residential and public buildings, there is a need to integrate systematic methodologies of technical control, digital technologies, and analytical tools for monitoring. Conceptual-categorial analysis of technical monitoring allows identifying the key concepts and methodological foundations that form the structure for assessing the condition of building assets, including engineering parameters, operational indicators, and risk factors. Particular attention is paid to modern data collection and processing technologies, such as IoT sensors, wireless surveillance systems, digital building models (BIM), as well as analytical algorithms for predicting defects and critical deviations in structural elements. A high level of integration of information systems with regulatory requirements and operational standards allows increasing the accuracy of technical condition assessments, ensuring timely response to emergency situations, and optimizing planned maintenance and reconstruction works. An important component is the consideration of external environmental factors, such as climatic conditions, load intensity, material aging, and technical features of structures, which directly affect the risks and reliability of assets. Furthermore, the integration of digital technologies enables the formation of a transparent resource and decision-making management system, where monitoring is not limited to state control but becomes an active tool for forecasting, planning, and investment optimization. Generalization of existing technical monitoring practices confirms that a comprehensive approach, combining analytics, digital models, and regulatory requirements, allows improving safety, efficiency, and economic feasibility of building asset operation, reducing risks of accidents and unforeseen costs.